1991
DOI: 10.1093/jn/121.7.1062
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B-6 Requirements of Elderly Men and Women

Abstract: The vitamin B-6 requirements of 12 men and women over 60 y old were studied. The protocol consisted of a 5-d baseline period and four experimental periods during which the subjects successively received 0.003, 0.015, 0.0225 and 0.03375 mg of vitamin B-6/(kg body wt.d). Dietary protein was 1.2 or 0.8 g/(kg body wt.d). At 5- or 6-d intervals, xanthurenic acid (XA) after a 5-g L-tryptophan load and 4-pyridoxic acid (4-PA) in 24-h urine, erythrocyte aspartate aminotransferase activity coefficient (EAST-AC) and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
40
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 27 publications
6
40
0
Order By: Relevance
“…Patients had low hemoglobin concentrations in our study; however, vitamin B6 status revealed no effect on hemoglobin concentration. This finding agrees with that of other studies (Ribaya-Mercado et al, 1991;Huang et al, 1998). Patients had low hemoglobin concentrations which may be caused by other factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients had low hemoglobin concentrations in our study; however, vitamin B6 status revealed no effect on hemoglobin concentration. This finding agrees with that of other studies (Ribaya-Mercado et al, 1991;Huang et al, 1998). Patients had low hemoglobin concentrations which may be caused by other factors.…”
Section: Discussionsupporting
confidence: 93%
“…Tébi et al (2000) reported that 590 diseased elderly people had an adequate mean EAST-AC level (1.75 AE 0.38). However, studies (Lui et al, 1985;Ribaya-Mercado et al, 1991) indicated that EAST-AC could be normal in the presence of chronic and marginal vitamin B6 deficiency. Therefore, EALT-AC rather than EAST-AC is a more sensitive indicator of vitamin B6 status (Brown et al, 1975;Leklem, 1990;Cochary et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma PLP concentration in elderly adults aged 65-75 y was lower than that in young adults aged 25-35 y, while dietary vitamin B6 intake and urinary 4-PIC were the same among these groups (24), consistent with the present results for age-related alteration of vitamin B6 metabolism obtained from the animal experiment. The vitamin B6 requirements of the elderly over 60 y were determined as 1.9-2.0 mg/d from their plasma PLP and urinary 4-PIC (25), and these values are higher than those reported for younger adults (26). An oral vitamin B6 loading study shows that vitamin B6 absorption and ability to synthesize PLP are not different between elderly and young adult (24).…”
Section: Discussionmentioning
confidence: 83%
“…Decrease in apoenzyme synthesis or in crease in apoenzyme degradation, and im pairment of PLP-binding sites have been pre viously suspected to explain preserved a-EAST values in chronic vitamin B6 deficiency [16]. Plasma PLP has been reported to be the most appropriate single index to use for nutri tional status surveys of elderly persons be cause a-EAST can appear normal in the pres ence of chronic and marginal vitamin B6 defi ciency [17][18][19], For vitamin C, plasma ascor bate values were always lower in subjects with infection as compared with both of the other groups.…”
Section: Discussionmentioning
confidence: 99%